Засоби захисту інформації від витоку по каналах мобільного зв’язку стандарту GSM - Гапич, І. Ю. (ХНУРЕ, 2024)
Methods of preventing information leakage through mobile communication channels were considered and a radio technical device for suppressing signals of the GSM standard was developed. The selection of the structural scheme of the denoising device of the mobile communication path of the GSM standard and its components, including the scheme of the two-channel noise generator (900 MHz and 1800 MHz), power amplifiers (PA) (transmission band 400–1500 MHz and 1400–2500 MHz) was, low-pass filter carried out.
Keywords: захист інформації від витоку; стандарт GSM